Comparative Analysis of Entrepreneurial Intention Among Students: A Cross-Country Study - Ovidiu Niculae Bordean; Zenovia Cristiana Pop; Nina Rizun; Reinhold Bopp; Tom Estad (SAGE Open)
Entrepreneurial intention (EI) is a predictor of entrepreneurial behavior. In past years, it received significant attention due to the numerous advantages of entrepreneurial activities. The formation of EI within diverse international settings has been studied by researchers; however, the results of these studies are still inconclusive. Building on the Theory of Planned Behavior (TPB), this study aims to shed light on how EI is created within three countries with different cultural, economic, and social backgrounds. Data was collected through a questionnaire completed by 413 business students enrolled in three universities in Germany, Romania, and Ukraine. Structural equation modeling analysis was used to examine the structure model of developing EI, and bootstrap confidence intervals were examined to test the mediating role, and multi-group analysis was used to identify differences among the three samples. Overall, the results reveal that both the attitude toward behavior (ATB) and the perceived behavior control (PBC) influence the EI of business students. These relationships were found to be significant in the three samples. ATB and PBC were identified as significant mediators of the relationship between social norms (SN) and EI in the overall sample. Within the subsamples, ATB was shown to have a mediation effect within the Ukrainian sample, whereas PBC was found to mediate the impact of SN on EI within the German and Ukrainian samples. The findings are discussed and both theoretical and practical implications are provided. JEL Clasification: L26, M13.